Brain Tumor-Induced Changes in Routine Parameters of the Lipid Spectrum of Blood Plasma and Its Short-Chain Fatty Acids - Larisa Obukhova; Natalia Shchelchkova; Igor Medyanik; Konstantin Yashin; Artem Grishin; Oksana Bezvuglyak; Ilkhom Abdullaev (Current Issues in Molecular Biology)
The aim of this research was to provide a comparative analysis of the major parameters of the blood lipid spectrum found both in the case of brain tumors and in atherosclerosis, as well as to assess the correlation of these indicators with the proliferative activity index Ki-67 in cells. Blood analyses were conducted on samples from 50 patients with brain tumors and 50 patients with cerebral atherosclerosis. Blood plasma from 50 essentially healthy people was used for controls. Significant differences were found in the parameter values between the atherosclerosis sufferers and the control group only for their ratios of neutral lipids to cholesterol. Of the short-chain fatty acids, butyric acid is of greatest interest due to the significant differences of its levels from the control group in the blood of both patients with meningiomas and of those with gliomas. Statistically significant correlation coefficients between the levels of the Ki-67 cell proliferation marker and, in particular, butyric acid were found when compared with the neutral lipids to cholesterol ratios. These identified parameters of the blood plasma lipid spectrum can be used for preoperative diagnostics of brain tumors. However, these ratios cannot be used as preoperative noninvasive predictors of the level of the Ki-67 mitotic index, as no significant differences corresponding to this were found for low-grade or for high-grade anaplasia of brain tumors.